Harmony Search-Based Cluster Initialization For Fuzzy C-Means Segmentation Of MR Images. - Moh’d Alia, Osama; Mandava, Rajeswari (2009)
We propose a new approach to tackle the well known fuzzy c-means (FCM) initialization problem.